The Effect of Using the Teams Games Tournament (Tgt) Method on Increasing Learning Outcomes in Reading Beam Notation at Sma Negeri 1 Tondano - Jaris Paulus Aait Banua; Orbanus Naharia; Marius Y. Lahea (Researchparks Publishing, 2022)
Studying music is a subject in schools where there is block notation, so this study aims to improve learning achievement in reading block notation of students in learning the art of music through the Teams Games Tournament model. This is because before the research was carried out, the basic music theory material, especially reading block notation, was a lesson that was less attractive to students, thus affecting the achievement achieved by students which was classified as low. The type of research used is Classroom Action Research (CAR) or Classroom Action Research with the Kemmis and Mc Taggart model which is carried out in 2 cycles. The research subjects were students of class X-2 of SMA Negeri 1 Tondano who took part in cultural arts classes, especially music arts, totaling 34 students. The data collection techniques used in this study were in the form of observation guidelines, documentation, and tests. Analysis of student achievement data was analyzed descriptively qualitatively and the percentage of completeness scores measured based on KKM (Minimum Completeness Criteria) at SMA N 1 Tondano. The study showed an increase in the ability to read block notation of class X-2 students, namely before the study the average score was 5.9 with the lowest score of 4.3 and the highest score of 8.5. After taking action in the first cycle, the average score was 7.3 with the lowest score being 5 and the highest score being 8.6. In this cycle, there were 12 students or 35.3% who had not reached the KKM at SMA N 1 Tondano. In cycle II the average score obtained by students is 7.9 with the lowest score being 7 and the highest score being 9.25. In this cycle there were 34 students or 94.1% who achieved the KKM in SMA 1 Tondano and students or 5.9% who had not reached the KKM in the SMA. The increase in value from before the action was carried out to the first cycle was 1.4, and the increase in value from the first cycle to the second cycle was 0.6. Based on the criteria for the success of the action, this research can be said to be successful. This is seen from the increase in the average score before the action to the second cycle is 2. Thus, it can be said that the application of the Teams Games Tournament model can improve the ability to read block notation of class X-2 SMA Negeri 1 Tondano. and the increase in value from cycle I to cycle II is 0.6. Based on the criteria for the success of the action, this research can be said to be successful. This is seen from the increase in the average score before the action to the second cycle is 2. Thus, it can be said that the application of the Teams Games Tournament model can improve the ability to read block notation of class X-2 SMA Negeri 1 Tondano. and the increase in value from cycle I to cycle II is 0.6. Based on the criteria for the success of the action, this research can be said to be successful. This is seen from the increase in the average score before the action to the second cycle is 2. Thus, it can be said that the application of the Teams Games Tournament model can improve the ability to read block notation of class X-2 SMA Negeri 1 Tondano.